2020
DOI: 10.1038/s41598-020-62811-4
|View full text |Cite
|
Sign up to set email alerts
|

Seasonal changes of circulating 25-hydroxyvitamin D correlate with the lower gut microbiome composition in inflammatory bowel disease patients

Abstract: Higher probability of the development of Crohn's disease (CD) and ulcerative colitis (UC) as a possible consequence of the north-south gradient has been recently suggested. Living far north or south of the equator is manifested in fluctuation of vitamin D (vitD) levels depending on the season in both healthy and affected individuals. In the present study we investigate the possible link between the seasonal serum vitD level to the microbial composition of the lower gut of Inflammatory Bowel disease (IBD) patie… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
26
0
2

Year Published

2020
2020
2023
2023

Publication Types

Select...
8
2

Relationship

0
10

Authors

Journals

citations
Cited by 31 publications
(30 citation statements)
references
References 74 publications
(59 reference statements)
2
26
0
2
Order By: Relevance
“…Unlike other studies, low levels of vitamin D were associated with a more balanced composition of the microbiome. It should be noted that it was not a randomized controlled trial (RTC), but vitamin D levels were correlated with changes in the microbiome in individuals with IBD [ 97 ].…”
Section: Vitamin D Critical Role In Ibdmentioning
confidence: 99%
“…Unlike other studies, low levels of vitamin D were associated with a more balanced composition of the microbiome. It should be noted that it was not a randomized controlled trial (RTC), but vitamin D levels were correlated with changes in the microbiome in individuals with IBD [ 97 ].…”
Section: Vitamin D Critical Role In Ibdmentioning
confidence: 99%
“…In particular, they identified lower level of Escherichia/Shigella in stool of UC patients and increased level of Bacteroidetes in the stool of CD patients accompanied by lower proportion of Clostridium spp . and higher proportion of Firmicutes in the mucosa [ 90 ]. Another study that evaluated samples of the intestinal mucosa found a decrease in gammaproteobacteria and increased Bacteroidetes in the microbiome of the upper gastrointestinal tract of patients receiving vitamin D supplementation without significant effects on terminal ileum, ascending colon, sigmoid colon, and stools [ 91 ].…”
Section: Vitamin D and Gut Microbiota Homeostasismentioning
confidence: 99%
“…Unlike other studies, low levels of vitamin D were associated with a more balanced composition of the microbiome. It should be noted that it was not a randomized controlled trial (RTC), but vitamin D levels were correlated with changes in the microbiome in individuals with IBD [80].…”
Section: Vitamin D and Gut Microbiota Modulationmentioning
confidence: 99%